DUVANSKA NARKOMANIJA I SPORTSKA RADNA SPOSOBNOST STUDENATA - Grujica Radunović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
A study performed at the Technology Faculty of the University of Podgorica confirms that smoking is a very hazardous habit among young people and clearly demonstrates that students who smoke suffer a definite reduction in bioenergetic potential during physical activity. Nicotine addiction is a far more dangerous habit than was once believed. Cigarette smoke is a mixture of miniature drops of katran which is composed of thousands of toxic substances. For this reason, the study was devised to investigate the effects of smoking on students' athletic abilities using the Cooper's running test of 2400 meters for men and 1600 for women. Three hundred students participated in the study of which 200 were male and 100 female. A total of 32% of participants were active, heavy smokers, 55% of these smokers being male and 26% female students. Results of the running test confirmed that nonsmoking males fmished in 11.04 min, while nonsmoking females fmished in 9.45 min. Student participants who were heavy smokers fmished the same test in 13.24 min. for males and 11.30 min for females. In both cases, a positive correlation was found for males of 0.87 and for females 0.90. It is clearly evident that students addicted to cigarette smoking obtained far worse results in the Cooper's running test of aerobic fitness as opposed to their counterparts who vvere light smokers or never smoked.